2007
DOI: 10.1080/00343400601142787
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Externalities, Local Industrial Structure and Economic Development: Panel Data Evidence for Morocco

Abstract: Bun M. J. G. and El Makhloufi A. (2007) Dynamic externalities, local industrial structure and economic development: panel data evidence for Morocco, Regional Studies 41, 823-837. The impact of industrial structure on local economic development is analysed for the case of Morocco. Using annual data for six urban areas and 18 industrial sectors indicators for specialization, diversity and competition of firms within a particular region are constructed for the years 1985-1995. The effects of these and other expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…Agglomeration of small-size firms in itself promoted external economies of scale captured under Porter-type local competition. This result contradicts those of Combes (2000), Bun and Makhloufi (2007) and Catin et al (2007). However, this result is not surprising.…”
Section: The Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Agglomeration of small-size firms in itself promoted external economies of scale captured under Porter-type local competition. This result contradicts those of Combes (2000), Bun and Makhloufi (2007) and Catin et al (2007). However, this result is not surprising.…”
Section: The Resultscontrasting
confidence: 59%
“…Examining 18 manufacturing sectors, the obtained results indicate that local employment growth positively depends on MAR and Jacobs externalities. Catin et al (2007) confirm the results found by Bun and Makhloufi (2007), using data on Moroccan provinces over the period of 1985-1999. Cota (2002 attempted to investigate the effect of agglomeration economies on the manufacturing sector of the northern border cities of Mexico.…”
Section: Agglomeration Economies Externalities and Regional Growth: mentioning
confidence: 84%
See 1 more Smart Citation
“…Recent non‐European evidence (Bun and El Makhloufi 2007) find positive effects of both specialization and diversity of local industrial structure on local industrial development using data for urban areas in Morocco for the period 1985–1995.…”
Section: The Effects Of Regional Specialization On Employment Growtmentioning
confidence: 99%
“…There is a growing number of empirical studies (for a brief survey see Bun and El Makhloufi 2007), which analyzes the relationship between knowledge externalities and economic development. The majority of these studies measures economic activity by employment and the sectoral perspective is introduced to take account of sector specific characteristics, which affect local historical industrial conditions.…”
Section: Introductionmentioning
confidence: 99%